PENGARUH SIZE DAN PROFITABILITAS TERHADAP MANAJEMEN PAJAK PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR PLASTIK DAN KEMASAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2020 - Intan Fitri (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2022)
Tax management is a management or strategy in the field of taxation to minimize the amount of tax burden in the company. The variables that can affect tax management in this study are size and profitability. The purpose of this study is to analyze and obtain empirical evidence regarding the effect of size and profitability on tax management. This study uses effective tax rates as an indicator in measuring tax management. The population in this study were 14 manufacturing companies in the plastic and packaging sub-sector listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020. Meanwhile, based on the criteria sought, there were 9 manufacturing companies in the plastic and packaging sub-sector that were obtained to be used as samples. The statistical method or analysis model used in this study is multiple regression analysis. The results of this study indicate that size has a positive effect on tax management. However, the results of profitability research show that profitability has no effect on tax management.